Supervision Planning at Islamic Education Institutions: Google Scholar Library Studies and Mendeley's Reference Manager - Imron Muttaqin (ISTAWA, 2020)
Supervision management is an important quality control mechanism to ensure education quality; this article provides an overview of the research findings concerning supervision management within Islamic education institution. This article divides the research findings broadly in two categories; “supervision planning”, supervision implementation and evaluation”. A qualitative approach used to understand the phenomena that occur, the data collected by reviewing and analyzing the literature sources using google scholar and Mendeley reference manager. The content analysis used to analyze supervision planning, implementing, and evaluating, which interprets as a method of analyzing the contents of the result. The research findings are; 1) supervision planning carried out with establishing the object, describing the purpose, needs identification, establishing the right indicator, determining an instrument, implementing, and following up 2) Implementation of supervision in Islamic Education Institutions using observation, managerial skill, using individual or group techniques, assessment and evaluation skill, and communication skills. For further research recommended, discuss the implementation of the supervision use Closed Circuit Television (CCTV) or integrated e-learning website.Manajemen supervisi merupakan mekanisme kendali mutu yang penting untuk menjamin mutu pendidikan; Artikel ini memberikan gambaran tentang temuan penelitian tentang manajemen supervisi di lingkungan institusi pendidikan Islam. Artikel ini membagi temuan penelitian secara luas menjadi dua kategori; “Perencanaan supervisi”, pelaksanaan supervisi dan evaluasi ”. Pendekatan kualitatif digunakan untuk memahami fenomena yang terjadi, pengumpulan data dilakukan dengan mereview dan menganalisis sumber pustaka menggunakan google scholar dan pengelola referensi Mendeley. Analisis isi digunakan untuk menganalisis perencanaan, pelaksanaan, dan evaluasi pengawasan yang diartikan sebagai metode menganalisis isi hasil. Temuan penelitian adalah; 1) Perencanaan supervisi dilakukan dengan menetapkan objek, mendeskripsikan tujuan, mengidentifikasi kebutuhan, menetapkan indikator yang tepat, menentukan instrumen, melaksanakan, dan menindaklanjuti 2) Pelaksanaan supervisi di Lembaga Pendidikan Islam dengan observasi, keterampilan manajerial, menggunakan individu atau teknik kelompok, keterampilan penilaian dan evaluasi, dan keterampilan komunikasi. Untuk penelitian selanjutnya disarankan membahas pelaksanaan supervisi menggunakan Closed Circuit Television (CCTV) atau website e-learning terintegrasi.